RISC GEOMORFOLOGIC LA OCNA MURES. Studiu de caz: Surparea din 22 decembrie 2010 (PANGEEA, 2025)
ABSTRACT: Geomorphological risk in Ocna Mures. Case Study: overthrow of December 22, 2010. The exploitation of salt in Ocna Mures began with the appearance of humans in this region, given the importance of salt in human nutrition. In Roman times, Salinae was a settlement of particular importance; the Roman road on the left side of Mures, from Apulum and Brucla (Aiud), reaching this settlement. A quantum leap occurred after 1792, when large-scale operation began in rooms as reverse funnel (cone), paralelipipedon or T. The human impact on the salt massif began with the introduction of technology to exploit the salt in a wet state. Keywords: salt mines; wells; geosistem; geomorphologic risk; subsidence; sustainable development.